Markets with a Continuum of Traders - Aumann, Robert J. (Econometrica, 1964)
It is suggested that the most natural mathematical model for a market with perfect competition is one in which there is a continuum of traders (like the continuum of points on a line). It is shown that the core of such a market coincides with the set of its allocations, i.e., allocations which constitute a competitive equilibrium when combined with an appropriate price structure.